IMPLEMENTASI KONSEP CRM PADA PEMASARAN ASESORIS KOMPUTER DI CV.STICOM BERBASIS ANDROID - yati nurhayati; Ade Rosidin (NUANSA INFORMATIKA, 2018)
CV. STICOM is a company engaged in the sale of computer equipment, computer accessories and repair services ,. In the process of marketing process is still done manually face to face. therefore there is a need for a system to streamline and streamline it all. The system that is built for the frontend includes the process of computer accessories information, the purchase of computer accessories, promo notifications, discounts and consultation complaints, While the backend system includes the management of purchase transactions, customer data, management of promo and discount info, data management complaints and monthly sales reports. In system development the author uses RUP (Rational Unified Process) method as a system development method. The repair service system made using two platforms for frontend using android, for backend using PHP and database using MySQL. From the built system can provide solutions for the process of marketing computer accessories have been computerized and communication media between consumers and companies become more effective and efficient.Keywords: Android, CRM Implementation, Marketing, PHP